'I Can't Go Back Because If I Go Back I Would Die': How Asylum Seekers Manage Talk about Returning Home by Highlighting the Importance of Safety. (8th November 2014) - Goodman, Simon; Burke, Shani; Liebling, Helen; Zasada, Daniel
Abstract Asylum seekers living in the UK have been shown to have fled danger in their countries of origin, only to face hardship and the threat of deportation once there. This paper draws on the discursive psychological approach to address the way in which asylum seekers in the UK manage questions about returning to their country of origin. Interviews were conducted with nine asylum seekers in a refugee support centre in the Midlands. The interviews were transcribed and analysed using discourse analysis. The analysis showed that participants drew on the notion of safety to counter suggestions that they should return to their country of origin and to manage their identity as legitimate asylum seekers in need of support. The use of this strategy and the use of interviews for discursive analysis are discussed. Copyright © 2014 John Wiley & Sons, Ltd.